Clinical characteristics and survival outcomes of patients with pneumonectomies: A population-based study - Wang, Linlin; Ge, Lihui; Zhang, Guofeng; Wang, Ziyi; Liu, Yongyu; Ren, Yi (Frontiers in Surgery, 2022)
Background: Prognostic factors in a pneumonectomy (PN) are not yet fully defined. This study sought to analyze and evaluate long-term survival after pneumonectomies (PNs) for patients with non-small cell lung cancer (NSCLC). Methods: We obtained data from the Surveillance, Epidemiology, and End Results (SEER) database for patients who underwent PNs between 2004 and 2015. Propensity score matching (PSM) analysis and Kaplan-Meier curves were used to estimate overall survival (OS), while univariate and multivariable Cox proportional hazards regression analyses were applied to create a forest plot. Results: In total, 1376 patients were grouped according to right/left PNs. Before matching, OS was worse after a right PN (hazard ratio [HR]: 1.459; 95% confidence interval [CI] 1.254–1.697; P<0.001) and after matching, survival differences between groups were not significant (HR: 1.060; 95% CI 0.906–1.240; P=0.465). Regression analysis revealed that age, gender, grade, lymph node dissection, N-stage, and chemotherapy were independent predictors of OS (P<0.05). Chemotherapy was associated with improved OS (P<0.001). Conclusions: Laterality was not a significant prognostic factor for long-term survival after a PN for NSCLC. Chemotherapy was a significant independent predictor of improved OS. Long-term survival and outcomes analyses should be conducted on larger numbers of patients.